2022
DOI: 10.1007/s00247-022-05363-1
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic shear wave elastography in children with type 1 diabetes: relation to diabetes duration, glycemic indices, fasting C-peptide and diabetic complications

Abstract: Background Little is known about changes in the pancreas as the course of type 1 diabetes progresses. Recently, shear wave elastography (SWE) emerged as a tool for assessing pancreatic stiffness in chronic pancreatitis and pancreatic cancer with a few studies assessing it in diabetes. Objective To compare pancreatic SWE in children with recent-onset and long-standing type 1 diabetes to healthy controls and to correlate it with diabetes duration, gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The median titer of IAA was 1.6, for IA2 it was 183.5, for GAD it was 10,6 and for ICA it was 1.4 in the T1D group and 1.35, 80.5 and 1.3, respectively, in the seropositive children receiving calcitriol or paricalcitol and did not differ significantly. This means that although T1Ab are related to the risk of T1D, they are not the primary mediators, and their presence or titers do not directly correlate with the degree of β-cell dysfunction [48].…”
Section: Discussionmentioning
confidence: 97%
“…The median titer of IAA was 1.6, for IA2 it was 183.5, for GAD it was 10,6 and for ICA it was 1.4 in the T1D group and 1.35, 80.5 and 1.3, respectively, in the seropositive children receiving calcitriol or paricalcitol and did not differ significantly. This means that although T1Ab are related to the risk of T1D, they are not the primary mediators, and their presence or titers do not directly correlate with the degree of β-cell dysfunction [48].…”
Section: Discussionmentioning
confidence: 97%
“…A study by Nouran et al. found that the levels of blood CP and 24-h UCP in T1DM patients were significantly lower than those in the control group and T2DM group, indicating poor secretion of insulin from the islet β-cells in T1DM patients ( 17 ). There were no significant differences in 24-h UCP between patients with normal renal function and patients with mild and moderate renal insufficiency, and 24-h UCP was positively correlated with blood CP ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strain imaging showed increased strain ratios in children with type 1 diabetes mellitus, presenting an additional method for early detection, long-term screening and follow-up in children with type 1 diabetes mellitus [ 54 ]. Similarly, shear wave imaging changed significantly with duration of type 1 diabetes mellitus, particularly in those with diabetic nephropathy and neuropathy [ 55 ], but not all studies confirmed that [ 56 ].…”
Section: Pancreas Ultrasound Elastography In Childrenmentioning
confidence: 99%